Perempuan, Mahluk Paling Super Dalam Islam : Women, The Most Superbe Creatures In Islam - Zainal Anshari (An-Nisa’ Journal of Gender Studies, 2015)
The issue of women experiencing discrimination in life does not only occur in one particular religion and is not a matter of interpretive bias as alleged by some Muslim scholars and Orientalists. However, discrimination is a human issue that occurs among all groups of people, regardless of religion and background. It is not only women who experience violence; it is not uncommon for men to also experience violence perpetrated by women. Similarly, violence against children is not only perpetrated by men, but also by women/mothers against their children. Therefore, in this context, Islam specifically gives women a very honorable place. As the Prophet said, first, a righteous woman is better than 70 righteous men. Second, whoever brings joy to his daughter, his status is like that of a person who constantly weeps out of fear of Allah (and those who fear Allah will be spared the fire of Hell). Therefore, it is unwise to blame Islam for its treatment of women. Masalah perempuan yang mengalami diskriminasi dalam kehidupan ini, bukan saja terjadi dalam satu agama tertentu dan bukan masalah keberpihakan tafsir sebagaimana dituduhkan oleh sebagian ilmuan muslim dan orientalis. Namun masalah diskriminasi adalah masalah kemanusiaann yang terjadi pada semua golongan manusia apapun agama dan latar belakangnya. Yang mengalami kekerasan bukan hanya perempuan, bahkan tidak jarang laki-laki juga mengalami kekerasan yang dilakukan oleh perempuan. Demikian juga kekerasan pada anak, bukan saja dilakukan oleh laki-laki, tapi juga dilakukan oleh perempuan / ibu kepada anak-anaknya. Oleh karenanya, dalam konteks ini, Islam secara spesifik memberikan ruang yang sangat terhormat kepada perempuan. Sebagaimana arahan nabi berikut ini, pertama, wanita yang solehah (baik) itu lebih baik daripada 70 orang pria yang soleh. Kedua, barang siapa yang menggembirakan anak perempuannya, maka derajatnya seumpama orang yang senantiasa menangis karena takut kepada Allah Swt (dan orang yang takut kepada Allah akan diharamkan api neraka atas tubuhnya). Sehingga tidak bijak, jika agama Islam dipersalahkan dalam perlakuannya kepada perempuan.